The Integration of Digital Technology into Physics Education for Sustainable Development: A Literature Review - Ike Anggraini Anggraini; Rahmatta Thoriq Lintangesukmanjaya; Dwikoranto Dwikoranto; Salma Hasna Hamiydah; Lindsay Natalia Bergsma; Neisya Azaria Adinda Putri (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to identify various forms of digital technology used in physics learning to support sustainable education, analyze how these technologies are integrated into the physics learning process, and examine the challenges and opportunities of implementing technology-enhanced physics education for sustainable development. Method: This study employed a qualitative approach, using a literature review to examine prior research on technology-enhanced physics education. The dataset consisted of 20 journal articles published between 2017 and 2025, retrieved from Scopus and Google Scholar. Results: The findings indicate that various forms of digital technology, such as simulations, virtual laboratories, augmented reality (AR), virtual reality (VR), and digital learning resources, are widely used in physics education. These technologies support the visualization of abstract physics concepts, increase students’ engagement and motivation, and improve conceptual understanding and problem-solving skills. The reviewed studies also show that digital technologies are frequently integrated with pedagogical approaches such as problem-based learning, flipped classroom learning, and scaffolding strategies to create more interactive and student-centered learning environments. In addition, several challenges were identified, including limitations in technological infrastructure and teachers’ readiness to integrate digital tools in teaching practices. Novelty: This study contributes to the existing literature by synthesizing recent research on integrating digital technology into physics education for sustainable development. It identifies the types of digital technologies, their pedagogical integration, and the challenges and opportunities associated with their implementation, providing insights for future research and the development of more effective technology-enhanced physics learning.